PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING TERHADAP KETERAMPILAN BERPIKIR KRITIS DAN HASIL BELAJAR IPA PADA SISWA KELAS V UPTD SD NEGERI 18 BARRU - Suardi Salama (JURNAL BANUA OGE TADULAKO, 2022)
Lack of student learning motivation results in students being less able to understand basic science concepts, so the quality of science education tends to be low. The purpose of this study was to determine the effect of the guided inquiry learning model on critical thinking skills and science learning outcomes in the experimental and control groups. The sample in this study consisted of 50 students. The data analysis technique used is descriptive statistical approach, N-Gain, and simple linear regression. The results showed that based on the data management hypothesis, it was obtained that there was an influence of the guided inquiry learning model on students' critical thinking skills. In addition, the N-Gain results show that as many as 24 students from the experimental class have increased critical thinking skills in the high category, while in the control class, only 10 students have increased critical thinking skills in the high category. The experimental class students' science learning outcomes showed that 20 students were in the high category and only 12 students from the control class were in the high category. So it can be concluded that guided inquiry in the field of science studies affects critical thinking skills and science learning outcomes for fifth grade students of UPTD SD Negeri 18 Barru, Barru Regency.